Comparative Overview on Standard and Tubeless Percutaneous Nephrolithotomy for Renal Calculi - Manu Muraleedharan Kamalakshi; Vasantharaja Ramasamy; Darsan Sadasivan; Sunil Raveendran; Selvam Paramasivam; Venugopal Ganapathy (Advanced Concepts in Medicine and Medical Research Vol. 9, 2023)
This chapter prospectively compared the outcome of tubeless PCNL (without nephrostomy drainage tube) to reduce the pain and discomfort caused by tube with standard PCNL in the treatment of renal stones. Percutaneous nephrolithotomy (PCNL) is the cornerstone of treatment for renal stones larger than 2 cm in the present era of minimally invasive treatments. PCNL saw a number of evolutionary developments that reduced patient morbidity. We conducted this prospective randomized control trial in the Department of Urology, Government medical college, Trivandrum, Kerala, South India during the period of July 2018 to April 2019 (10 months). Patient’s age, gender, sides of stone and stone size were comparable between two groups (standard versus tubeless PCNL). Postoperative hemoglobin drop, bleeding, pyrexia, urine leak, and blood transfusion requirement did not show a statistically significant difference between the two groups. Postoperative urine leak and pyrexia were seen in only one patient in the standard PCNL group and none in the tubeless PCNL group showing statistically insignificant results. Analgesic requirement (190 mg versus 80 mg of tramadol), operative duration (49.80 min versus 38.60 min), postoperative pain score (6/10 versus 3.64/10-visual analog scale) and duration of hospital stay (68.48 hours versus 41.12 hours) showed statistically significant difference favoring tubeless PCNL. Tubeless PCNL although showed promising results overall less morbidity in our trial should be preferred only in carefully selected patients with no residual stones, no bleeding or injury, no complex stone or abnormal kidney anatomy to avoid any complications postoperatively.